Analysis the Influence of Online Learning on Students' Learning Enthusiasm - Almira Faramadila Putri; Muhamad Sofian Hadi; Lidiyatul Izzah (STKIP Singkawang, 2021)
This research was created to explain in detail how the objective conditions of decreased enthusiasm for learning experienced by students in online learning during the covid-19 pandemic. This research uses quantitative methods with survey techniques. This research was conducted by involving 10 high school or vocational high school students. The data collection technique used in this study was a survey technique with a Likert scale. The survey was created in Microsoft Word and then distributed via WhatsApp to make it easier to access. The data analysis technique used in this study was to calculate the percentage of data on each indicator, then interpret the presentation score and analyze each indicator in detail. The inal results of the study indicate that the decline in learning of high school or vocational high school students is considered to be less good, it is obtained from the percentage score which amounts to 45%. Hope this reseacrh can be an evaluation of various parties in implementing online learning, especially those involving motivation and enthusiasm for learning in it. In addition, it is hoped that it van be use as research material for other researchers in analyzing and developing students’ enthusiasm for learning in online learning during emergencies.